Functionalization of bamboo-like carbon nanotubes with 3-mercaptophenylboronic acid-modified gold nanoparticles for the development of a hybrid glucose enzyme electrochemical biosensor - Eguílaz Rubio, Marcos (2015)
We report for the first time a sensitive and selective glucose biosensor based on the immobilization at glassy carbon electrodes (GCE) of a new hybrid nanomaterial consisting of gold nanoparticles functionalized with 3-mercaptophenyl boronic acid (AuNPs-B(OH)2) and bamboo-like multiwall carbon nanotubes (bMWCNT) dispersed in hyperbranched polyethyleneimine (PEI). The presence of boronic acid residues allowed the supramolecular immobilization of glucose oxidase (GOx) as a model glycoenzyme while the hybrid nanomaterial Au(NP)-bMWCNT produces a synergistic effect on the catalytic detection of the enzymatically generated hydrogen peroxide. The resulting functionalized nanomaterials were characterized by TEM, FT-IR and electrochemical techniques. The sensitivity at 0.700 V was (3.26 ± 0.03) mA M−1 (28.6 mA M−1 cm−2), with a linear range between 2.50 × 10−4 M and 5.00 × 10−3 M, a detection limit of 0.8 μM and a quantification limit of 2.4 μM. The biocatalytic layer demonstrated to be highly reproducible with R.S.D. values of 8.6% for 10 successive amperometric calibrations using the same surface, and 4.5% for ten different bioelectrodes. The sensitivity of the biosensor after 14 days of storage at 4 °C remained at 86.1% of its original value. The combination of the excellent dispersing properties of PEI, the stability of the bMWCNT-PEI dispersion, the synergistic effect of AuNPs-B(OH)2 and bMWCNT towards the electrooxidation of hydrogen peroxide, and the robust immobilization of GOx at AuNP-B(OH)2 allowed building a sensitive, reproducible and stable amperometric biosensor for the quantification of glucose in beverages and milk samples.